Self-transcendence and quality of life in assistants to a Chair for the Elderly in Cumanayagua, Cuba - Izaguirre-Bordelois, Marioneya (2021)
Introduction: Aging is a worldwide population phenomenon, which generates an increasingly numerous group of older adults with the consequent physical and mental deterioration at that age, for which it is necessary to establish mechanisms, policies and attitudes that favor dignified aging, The Chairs for the Elderly have been an ideal space to achieve this objective. The purpose of the present study was to determine the level of self-transcendence of older adults attending a University Chair for the Elderly and the impact on their quality of life. Method: A cross-sectional descriptive study of 65 older adults enrolled in one of these chairs was carried out during the 2017-2018 school period, in the town of Cumanayagua in the Cienfuegos province (Cuba). To obtain the necessary information, an in-depth interview was applied and the self-transcendence scale of Pamela G. Reed (1987) was applied. Results: The average age of the elderly was 73.5 years, and 68.7% were female. The level of self-transcendence of the older adults studied was high. Conclusion: It has been shown that these contexts bring together people of different age, sex, schooling and areas of residence and also favor raising the level of self-transcendence of enrolled adults and improving their quality of life.